Buprenorphine for the management of kratom dependency during covid-19: A case report. (July 2021) - Gittins, Rosalind; Cole, Samantha
We describe a case report where buprenorphine was successfully used for the management of kratom ( Mitragyna speciosa ) dependency during the Covid-19 pandemic in a specialist community substance misuse treatment service. The individual had a notable iatrogenic dependency on oral over the counter and prescribed opioid medication. She resorted to using kratom as a 'tea' to self-detoxify before getting into difficulty. Upon presentation, she disclosed using kratom up to 70 g/day with hourly dosing, in addition to co-codamol (8 mg codeine/500 mg paracetamol tablets) three times a week. Initiation of oral buprenorphine sublingual tablets was complicated due to Covid-19: dispensing arrangements were liberalised from the outset and the dose was incrementally increased, eventually to 24 mg/day. Comorbidities included mental health conditions and chronic pain which improved with buprenorphine treatment and psychotherapy. Further research is required to determine optimal regimens for the management of kratom dependency. This case study adds to the current paucity of published data regarding how to manage such cases in the community setting, which is important since kratom is thought to be increasingly used in the western world.